Remembering The Civil War in Today’s Lebanese Cinema - Evecen, Gökhan; Serter, Sırrı Serhat (CINEJ cinema journal, 2025)
In the aftermath of the civil war, memory and trauma are a prominent thema in Lebanese cinema. This study aims to explore how the civil war is remembered through cinema in contemporary Lebanese cinema, based on an analysis of the films Where Do We Go Now?, Tramontane, The Insult and Memory Box. These films, selected from among the films made in Lebanon after 2010 by Lebanese directors and dealing with the civil war, were analysed through descriptive analysis under the themes of past, identity, trauma and space. The films under scrutiny serve as conduits for the articulation of remembrance, both as a means of confronting past traumas and of reflecting upon the present. The act of remembering the past and confronting traumas is rendered through the medium of personal recollections by the directors, thus creating a narrative of collective memory. When the subject of the civil war is represented in films, it is commonly remembered as “the past in the present”.